Adventure Tourism and Regional Socio-Economic Transformation in Assam: Development of the AT-RST Framework: Adventure Tourism and Regional Socio‑Economic Transformation in Assam: Development of the AT‑RST Framework - Abu Samet Barbhuiya (Language Assistance, 2026)
Adventure tourism is a rapidly growing global sector with significant potential for regional socio-economic development, especially in peripheral regions like Assam, Northeast India. Despite Assam’s rich natural and cultural assets, limited research exists on its tourism-driven transformation. This study explores adventure tourism’s role in Assam’s development and introduces the Adventure Tourism–Regional Socio-Economic Transformation (AT-RST) Framework as an integrated conceptual model. Using secondary data from government reports, policy documents, and academic literature, the study examines Kaziranga and Manas National Parks to illustrate tourism impacts. Findings indicate that adventure tourism fosters employment, entrepreneurship, infrastructure, livelihood diversification, and community participation, contributing to regional economic change. However, successful outcomes depend on the interplay between tourism resources, infrastructure, governance, and local engagement. The AT-RST Framework offers a theoretical lens to explain these dynamics and supports structured planning for emerging destinations. While the study enriches the literature on adventure tourism and regional development, it is limited by its reliance on secondary data and case-study scope. Future primary and mixed-method research is recommended for further validation. The findings provide actionable policy insights for sustainable, inclusive tourism planning in Assam, helping stakeholders maximize socio-economic benefits while safeguarding environmental sustainability.